Natural disasters as a source of entrepreneurial opportunity: Family business resilience after an earthquake - Salvato, Carlo; Sargiacomo, Massimo; Amore, Mario Daniele; Minichilli, Alessandro (Strategic Entrepreneurship Journal, 2020)
Abstract Research Summary What type of firms are more likely to survive or even thrive in disaster events such as earthquakes, wildfires, and the COVID‐19 pandemic? We investigate whether family ownership and industry positioning affect firms' ability to capture opportunities for business recovery after a natural disaster. We analyze the performance of Italian family and nonfamily firms around a disastrous earthquake in 2009. Following the earthquake, family firms performed better than nonfamily firms, especially when multiple family members were involved as owners. Moreover, family ownership is beneficial in industries highly dependent on the public sector. Our findings provide evidence on the superior resilience of family firms by illustrating the characteristics that allow firms hit by disaster events to seize posttraumatic entrepreneurial opportunities for recovery and growth. Managerial Summary The purpose of this study was to understand whether a possible explanation of family firms' superior longevity is their resilience to mass emergencies and their ability to transform post‐crisis threats into entrepreneurial opportunities. We found that family firms performed better than their nonfamily peers after the earthquake that hit Central Italy, and especially the area around L'Aquila, in 2009. During disaster events, family ownership resources—focused on the long term and the desire to transfer the business to future generations—provide the firm with the social and emotional capital needed to address the hardship. Moreover, family firms that operated in industries closer to the public demand leveraged the family proximity to politics, further enhancing the processes of recovery and opportunity identification.